2019
DOI: 10.1002/ppul.24465
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into biomarkers for the diagnosis of ABPA and aspergillus disease in cystic fibrosis

Abstract: Background Allergic bronchopulmonary aspergillosis (ABPA) is a hypersensitivity lung disease due to Aspergillus fumigatus (Af) which occurs in 10% of patients with cystic fibrosis (CF). ABPA is associated with increased morbidity and accelerated lung function decline; however, existing diagnostic criteria are nonspecific and diagnosis remains challenging. As ABPA is driven by Th2 inflammation, the aim of this study was to evaluate exhaled nitric oxide (FE NO), eosinophilic cationic protein (ECP), peripheral eo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…However, a positive culture for Aspergillus from sputum does not imply the development of ABPA because of the heterogeneity of the interaction between the fungus and the host. In fact, allergy to Aspergillus antigens detected by skin prick test is described in almost 50% of CF patients, whilst the prevalence of ABPA is estimated to be between 10% and 25% depending on the studies [ 10 , 11 , 12 , 13 , 14 ]. However, ABPA may be often underdiagnosed due to the lack of standardized diagnostic criteria.…”
Section: Epidemiology Of Aspergillus Fumigatus mentioning
confidence: 99%
“…However, a positive culture for Aspergillus from sputum does not imply the development of ABPA because of the heterogeneity of the interaction between the fungus and the host. In fact, allergy to Aspergillus antigens detected by skin prick test is described in almost 50% of CF patients, whilst the prevalence of ABPA is estimated to be between 10% and 25% depending on the studies [ 10 , 11 , 12 , 13 , 14 ]. However, ABPA may be often underdiagnosed due to the lack of standardized diagnostic criteria.…”
Section: Epidemiology Of Aspergillus Fumigatus mentioning
confidence: 99%
“…Sometime, bronchospasms are present. In CF patients, ABPA is not a rare disease; in most studies, it was reported that it was diagnosed in approximately 10% of cases [6,7]. Despite its relative frequency, the significant clinical manifestations and the characteristic laboratory findings, ABPA is frequently underdiagnosed, and diagnosis is frequently made several months or years after the onset of signs and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…of ABPA in CF. 5,6 It has been assessed that an early disease recognition may prevent the progression of ABPA, and accordingly, clinical and radiographic stages of ABPA progression have been proposed. 3,7 The radiographic findings of ABPA on chest-X-ray are not specific, but pulmonary infiltrates, consolidation, and macronodular densities are commonly reported at the early-stage disease, whereas central bronchiectasis, ring shadows, and pulmonary fibrosis are reported at the end-stage.…”
mentioning
confidence: 99%
“…Patients with ABPA show a severe progression in all lung function parameters, and FEF at 50% VC (FEF 50 ), the volume of trapped gas, and specific airway resistance as the best predictors have been reported 1,2,4 . Recently, exhaled nitric oxide (FE NO ) has been proposed as biomarker for the diagnosis of ABPA in CF 5,6 . It has been assessed that an early disease recognition may prevent the progression of ABPA, and accordingly, clinical and radiographic stages of ABPA progression have been proposed 3,7 .…”
mentioning
confidence: 99%